Peran Sosial Media Dalam Memperngaruhi Opini Publik Terhadap Perkembangan Isu Pendidikan di Indonesia - Wulandari, Desi; Saputri, Fany; Nabila, Putri Sukma; Syuja, Athallah Rafif (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Social media is certainly a benchmark for important tools for life, especially in communication that greatly influences public opinion. Social media users themselves have a positive impact on a process between social interaction processes, both from politics and economics. Then also in general it can influence the views and attitudes of society. In the world of education, social media is also active because many people or groups are circulating about educational issues that must be digested properly because social media itself also has a negative impact if the city does not filter news about circulating issues properly which will cause its own chaos.